News values on social media: Exploring what drives peaks in user activity about organizations on Twitter. (May 2020) - Araujo, Theo; van der Meer, Toni GLA
Since news circulation increasingly takes place online, the public has gained the capacity to influence the salience of topics on the agenda, especially when it comes to social media. Considering increased scrutiny about organizations, this study aims to understand what causes heightened activity to organization-related topics among Twitter users. We explore the extent to which news value theory, news coverage, and influential actors can explain peaks in Twitter activity about organizations. Based on a dataset of 1.8 million tweets about 18 organizations, the findings show that the news values social impact, geographical closeness, facticity, as well as certain influential actors, can explain the intensity of online activities. Moreover, the results advocate for a more nuanced understanding of the relation between news media and social media users, as indications of reversed agenda-setting patterns were observed.